Project Management and File Management in Multimedia Applications Version of ActionScript 2.0 - Hardiyana, Bella; Effendi, Diana (Universitas Komputer Indonesia, 2023)
Multimedia is a key focus within the Information Systems Study Program at Universitas Komputer Indonesia. With increasing student interest and certification from the National Professional Certification Agency, more students are producing quality multimedia theses. However, many lack understanding of theoretical principles such as project and file management, which this research aims to address for both academic and real-world applications. This research was conducted at PS-SI UNIKOM. The research data was taken from the collection of thesis students of the UNIKOM PS-SI even semester academic year 2019/2020. The focus of this research is using the Adobe Flash CS 6 version ActionScript 2.0 approach. This study expects students to understand multimedia scientific principles and implement them in a real thesis and multimedia project. Implementing project management and file management in the multimedia field will help developers develop multimedia application products effectively and efficiently.